Exploring the macroeconomic drivers of international bilateral-remittance flows: A gravity-model approach - Giorgio Fagiolo; Tommaso Rughi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
This paper investigates the macroeconomic determinants of global bilateral remittances flows. Using data covering 216 World countries over the 2010-2017 period, we employ a gravity-model approach to explore the role payed by dyadic and country-specific covariates in explaining remittances. Robustly across alternative estimation techniques and specifications, we find that remittance flows are strongly impacted by size effects (i.e., number of migrants in the host country and population at home); transaction costs; common social, political and cultural ties; output growth rate and financial development in the home country. We also document the existence of a robust non-linear relationship between per-capita income at home and remittance flows, which we study both in the aggregate and in subsamples where home and host countries are categorized according to their income group. Overall, our results suggest that altruistic and self-interested motives non-trivially interact and may change across both host/home income groups and the level of income at home.
Keywords: F24; F22; F63; 330; International remittances; International migration; Gravity Models